Sodium ion capacitor taking coal-based porous graphene-like carbon material as positive electrode and preparation method of sodium ion capacitor
By using coal-based porous graphene carbon material as the cathode of sodium ion capacitors, the problems of low capacity and high cost of traditional cathode materials are solved, and high capacity, high speed and low cost energy storage effects are achieved.
Patent Information
- Application Number
- CN202510548186.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-28
- Publication Date
- 2025-06-10
AI Technical Summary
The cathode material of traditional sodium ion hybrid capacitors has low capacity, poor rate performance and high cost, which limits its application and commercialization development.
A porous graphene carbon material with a high specific surface area and a high degree of graphitization was prepared by pre-carbonizing the coal material and heating it with potassium hydroxide in an inert atmosphere.
The adsorption and storage capacity of sodium ions is improved, the charge transfer rate and power density are improved. At the same time, due to the abundant coal-based resources and low cost, a low-cost large-scale preparation of energy storage devices is achieved.
Smart Images

Figure CN120126941A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium-ion capacitors, and particularly relates to a sodium-ion capacitor with a coal-based porous graphene-like carbon material as the positive electrode and a preparation method thereof. Background Art
[0002] Sodium-ion batteries and supercapacitors, as two types of complementary electrochemical energy storage systems, have broad application prospects in the fields of electric vehicles, power grid peak shaving, and portable electronic devices. Compared with the increasingly scarce lithium resources and continuously rising prices, sodium resources are rich in reserves and low in price. Therefore, energy storage devices based on sodium ions have gradually attracted attention.
[0003] Sodium-ion hybrid capacitors (SIHC) integrate the advantages of high energy density of sodium-ion batteries and high power density of supercapacitors, and have long cycle life and fast charge and discharge capabilities, and have become an emerging direction for large-scale energy storage. Traditional positive electrodes of sodium-ion hybrid capacitors mostly use activated carbon materials, but there are problems such as low specific capacity, poor rate performance, and high cost, which limit their application and commercial development. Summary of the Invention
[0004] In order to overcome the problem of low capacity of the positive electrode material of the existing sodium-ion hybrid capacitor, the purpose of the present invention is to provide a sodium-ion capacitor with a coal-based porous graphene-like carbon material as the positive electrode and a preparation method thereof.
[0005] The technical solution adopted by the present invention is as follows: A sodium-ion capacitor with a coal-based porous graphene-like carbon material as the positive electrode includes a negative electrode plate. A separator containing an electrolyte is provided on the surface of the negative electrode plate. A positive electrode plate is provided on the surface of the separator containing the electrolyte. The active material of the positive electrode plate uses a coal-based porous graphene-like carbon material; the negative electrode material of the negative electrode plate uses graphite, hard carbon, soft carbon, lithium titanate, niobium-based oxide, niobium-based metal oxide, or titanium niobium oxide material; in the separator containing the electrolyte, the electrolyte uses an organic solution of sodium hexafluorophosphate.
[0006] Preferably, the preparation process of the positive electrode plate includes: Mix and grind the coal-based porous graphene-like carbon material, conductive agent, and binder into a film, and then perform vacuum drying to obtain the positive electrode plate.
[0007] Preferably, the mass ratio of the coal-based porous graphene-like carbon material, conductive agent, and binder is (6-8):1:1, and the surface density of the positive electrode plate is 0.9~1.1 g / cm 2 .
[0008] Preferably, the conductive agent uses one of conductive carbon black, acetylene black, and carbon nanotubes.
[0009] Preferably, the binder is one of polyvinylidene fluoride, polytetrafluoroethylene, and sodium carboxymethyl cellulose.
[0010] Preferably, the preparation process of the coal-based porous graphene carbon material includes: Heating the coal material at a heating rate of 8 - 10 °C / min to 690 - 710 °C, and holding for 1 - 2 h to obtain pre-carbonized carbon powder; Mixing the pre-carbonized carbon powder and potassium hydroxide in a mass ratio of 1:(4 - 6), then heating to 950 - 980 °C in an inert atmosphere and holding for activation for 1 - 2 h, and cooling after the holding ends to obtain a porous graphene carbon material; Washing the porous graphene carbon material repeatedly with hydrochloric acid and hydrofluoric acid 3 - 5 times, then washing with deionized water until the solution is neutral, and then drying to obtain the coal-based porous graphene carbon material.
[0011] Preferably, the separator is a glass fiber separator, and the electrolyte is filled in the pores of the glass fiber separator; In the electrolyte, the organic solution is a solution formed by mixing ethylene carbonate, diethyl carbonate, and dimethyl carbonate in an equal volume ratio, and the concentration of sodium hexafluorophosphate is 0.95 - 1.05 mol / L -1 .
[0012] Preferably, the preparation process of the negative electrode sheet includes: Adding the negative electrode material, acetylene black, and polyvinylidene fluoride to 1-methyl-2-pyrrolidone to form a slurry, coating it on the current collector, and then performing vacuum drying to obtain the negative electrode sheet; wherein, the mass ratio of the negative electrode material, acetylene black, and polyvinylidene fluoride is (75 - 85):10:10.
[0013] Preferably, the negative electrode material, acetylene black, and polyvinylidene fluoride are added to 1-methyl-2-pyrrolidone in an equal mass ratio to form a slurry, and the total volume of the negative electrode material, acetylene black, and polyvinylidene fluoride is equal to the volume of 1-methyl-2-pyrrolidone.
[0014] The preparation method of the sodium-ion capacitor using the coal-based porous graphene carbon material as the positive electrode as described above in the present invention includes; Assembling in the order of the negative electrode sheet, the separator containing the electrolyte, and the positive electrode sheet in a protective atmosphere to obtain the sodium-ion capacitor using the coal-based porous graphene carbon material as the positive electrode.
[0015] The present invention has the following beneficial effects: The sodium-ion capacitor with a coal-based porous graphene-like carbon material as the positive electrode has the following advantages compared with the traditional activated carbon positive electrode: (1) Ultra-high specific surface area: It provides abundant sites for the adsorption and storage of sodium ions, improving the capacity; (2) High graphitization degree: It enhances the electron / ion conductivity, accelerates the charge transfer rate, and improves the power density; (3) Abundant coal-based resources and low cost: It is conducive to the large-scale and low-cost preparation of energy storage devices. Description of the Drawings
[0016] Figure 1 It is the GCD test curve of the coal-based porous graphene-like carbon material prepared in Example 1 of the present invention.
[0017] Figure 2 It is the CV test chart of the coal-based porous graphene-like carbon material prepared in Example 1 of the present invention.
[0018] Figure 3 It is the GC chart of the coal-based porous graphene-like carbon material prepared in Example 1 of the present invention.
[0019] Figure 4 It is the GCD test curve of the sodium-ion capacitor prepared by assembling the positive electrode coal-based porous graphene and the negative electrode titanium niobium oxide material in Example 1 of the present invention.
[0020] Figure 5 It is the Ragone chart of the sodium-ion capacitor prepared by assembling the positive electrode coal-based porous graphene and the negative electrode titanium niobium oxide material in Example 1 of the present invention. Detailed Embodiments
[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are some, but not all, of the embodiments of the present invention. Usually, the components described and shown in the drawings here can be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts fall within the scope of protection of the present invention.
[0022] The sodium-ion capacitor with a coal-based porous graphene-like carbon material as the positive electrode includes: a positive electrode plate, a negative electrode plate, a separator, and an electrolyte. The active material of the positive electrode plate uses a coal-based porous graphene-like carbon material; the negative electrode material of the negative electrode plate uses one of graphite, hard carbon, soft carbon, lithium titanate, niobium-based oxide, niobium-based metal oxide, and titanium niobium oxide material; the hybrid capacitor is assembled in the order of the negative electrode plate, the separator containing the electrolyte, and the positive electrode plate to form the sodium-ion capacitor with a coal-based porous graphene-like carbon material as the positive electrode.
[0023] The separator can use glass fiber. Use a pipette to drop the electrolyte onto the glass fiber separator so that the electrolyte fills the pores of the glass fiber separator to obtain the separator containing the electrolyte; the electrolyte uses an organic electrolyte suitable for sodium ion transmission, such as using sodium hexafluorophosphate (NaPF 6 ), as the salt, dissolved in a mixed solution of ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC). In this mixed solution, ethylene carbonate, diethyl carbonate, and dimethyl carbonate are mixed in equal volume ratios; in the electrolyte, the concentration of sodium hexafluorophosphate is 0.95 - 1.05 mol L -1 .
[0024] The preparation of the active material coal-based porous graphene-like carbon material of the positive electrode plate includes the following steps: (1) Heat the coal material at a rate of 8 - 10 °C / min - 20 °C / min to 690 - 710 °C and keep it warm for 1 - 2 h for pre-carbonization to obtain pre-carbonized carbon powder; (2) Mix the pre-carbonized carbon powder obtained in step (1) and potassium hydroxide in a mass ratio of 1:(4 - 6), and then heat it to 950 - 980 °C in an inert atmosphere (such as argon) for activation, keep it warm for 1 - 2 h and then cool it to room temperature to obtain porous graphene carbon material; (3) Wash and remove impurities from the porous graphene carbon material obtained in step (2) with HCl and HF, and then wash it with deionized water until it is neutral and then dry it to obtain the coal-based porous graphene-like carbon material.
[0025] The capacitor assembly method is as follows: Positive electrode preparation: Mix the coal-based porous graphene-like carbon material, conductive agent, and binder in a mass ratio of (6 - 8):1:1 and grind them into a film, dry it in vacuum at 105 - 115 °C for 10 - 14 h, and tear off a 0.9 - 1.1 mg film to obtain a single-piece electrode of about 1 cm², that is, the positive electrode plate; in the above scheme, the conductive agent uses one of conductive carbon black, acetylene black, and carbon nanotubes; the binder uses one of polyvinylidene fluoride, polytetrafluoroethylene, and sodium carboxymethyl cellulose; Preparation of negative electrode sheet: Weigh the negative electrode material, acetylene black, and polyvinylidene fluoride according to the mass ratio of (75 - 85):10:10. Then add 1-methyl-2-pyrrolidone to form a slurry, coat it on the current collector, and dry it in vacuum at 60 - 90 °C for 12 - 18 h. Among them, the current collector of the negative electrode sheet is one of copper foil, aluminum foil, carbon paper, and carbon cloth, and the total volume of the negative electrode material, acetylene black, and polyvinylidene fluoride is equal to the volume of 1-methyl-2-pyrrolidone.
[0026] Assembly: Under the atmosphere of high-purity argon, assemble the negative electrode sheet, the separator containing the electrolyte, and the positive electrode sheet in sequence into the sodium-ion capacitor with the coal-based porous graphene carbon material as the positive electrode. This sodium-ion capacitor is a button-type sodium-ion capacitor.
[0027] Example 1 The sodium-ion capacitor with the coal-based porous graphene carbon material as the positive electrode in this example includes: a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. The active material of the positive electrode sheet uses the coal-based porous graphene carbon material; the negative electrode material of the negative electrode sheet uses titanium niobium oxide material; the hybrid capacitor is assembled into the sodium-ion capacitor with the coal-based porous graphene carbon material as the positive electrode in the order of the negative electrode sheet, the separator containing the electrolyte, and the positive electrode sheet.
[0028] The separator uses glass fiber. Use a pipette to drop the electrolyte onto the glass fiber separator so that the electrolyte fills the pores of the glass fiber separator to obtain the separator containing the electrolyte; the electrolyte uses an organic electrolyte suitable for sodium ion transmission. This electrolyte uses sodium hexafluorophosphate (NaPF 6 ) as the salt and is dissolved in a mixed solution of ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC). In this mixed solution, ethylene carbonate, diethyl carbonate, and dimethyl carbonate are mixed in equal volume ratios; in the electrolyte, the concentration of sodium hexafluorophosphate is 1.0 mol L -1 .
[0029] The preparation of the active material coal-based porous graphene carbon material of the positive electrode sheet includes the following steps: (1) Heat the coal material to 700 °C at a rate of 8 °C / min and hold for 1.5 h for pre-carbonization to obtain pre-carbonized carbon powder; (2) Mix the pre-carbonized carbon powder obtained in step (1) and potassium hydroxide in a mass ratio of 1:4, then heat it in argon to 950 °C for activation, hold for 2 h, and then cool to room temperature to obtain porous graphene carbon material; (3) Wash and remove impurities from the porous graphene carbon material obtained in step (2) with HCl and HF, then wash it with deionized water until neutral and dry it to obtain the coal-based porous graphene carbon material.
[0030] The method for assembling a capacitor is as follows: Preparation of the positive electrode: Mix a coal-based porous graphene carbon material, a conductive agent, and a binder in a mass ratio of 8:1:1 and grind them into a film. Vacuum dry the film at 110 °C for 12 h, and tear off 1.0 mg of the film to obtain a single-piece electrode of 1 cm², which is the positive electrode plate; in the above solution, the conductive agent is acetylene black; the binder is 60% polytetrafluoroethylene emulsion; Preparation of the negative electrode plate: Weigh the negative electrode material, acetylene black, and polyvinylidene fluoride in a mass ratio of 80:10:10, then add 1-methyl-2-pyrrolidone to form a slurry, coat it on the current collector, and vacuum dry it at 80 °C for 12 h; among them, the current collector of the negative electrode plate is copper foil, and the total volume of the negative electrode material, acetylene black, and polyvinylidene fluoride is equal to the volume of 1-methyl-2-pyrrolidone.
[0031] Assembly: Under an atmosphere of high-purity argon, assemble the negative electrode plate, the separator containing the electrolyte, and the positive electrode plate in sequence to form the sodium-ion capacitor with the coal-based porous graphene carbon material as the positive electrode. This sodium-ion capacitor is a button-type sodium-ion capacitor.
[0032] As Figure 1 shown, the constant current charge-discharge curve of the coal-based porous graphene carbon material obtained in this example is an isosceles triangle, indicating that the energy storage mechanism of the porous graphene carbon material is a standard capacitive behavior.
[0033] As Figure 2 shown, the half-cell of the coal-based porous graphene carbon material obtained in this example can maintain 88% of its capacity after 5000 cycles.
[0034] As Figure 3 shown, the CV curve of the sodium-ion capacitor constructed with the coal-based porous graphene carbon material obtained in this example presents a quasi-rectangle.
[0035] As Figure 4 shown, the constant current charge-discharge curve of the sodium-ion capacitor obtained in this example is an isosceles triangle, indicating that the constructed sodium-ion capacitor has a standard capacitive behavior.
[0036] As Figure 5 shown, the maximum energy density of the sodium-ion capacitor obtained in this example is 110 Wh / kg, and the maximum power density is 17.5 kW / kg.
[0037] Example 2 The sodium-ion capacitor with a coal-based porous graphene-like carbon material as the positive electrode in this embodiment includes: a positive electrode plate, a negative electrode plate, a separator, and an electrolyte. The active material of the positive electrode plate uses a coal-based porous graphene-like carbon material; the negative electrode material of the negative electrode plate uses graphite; the hybrid capacitor is assembled in the order of the negative electrode plate, the separator containing the electrolyte, and the positive electrode plate to form the sodium-ion capacitor with a coal-based porous graphene-like carbon material as the positive electrode.
[0038] The separator uses glass fiber. A pipette is used to drop the electrolyte onto the glass fiber separator so that the electrolyte fills the pores of the glass fiber separator to obtain the separator containing the electrolyte; the electrolyte uses an organic electrolyte suitable for sodium ion transmission. This electrolyte uses sodium hexafluorophosphate (NaPF 6 ) as the salt and is dissolved in a mixed solution of ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC). In this mixed solution, ethylene carbonate, diethyl carbonate, and dimethyl carbonate are mixed in equal volume ratios; in the electrolyte, the concentration of sodium hexafluorophosphate is 0.95 mol L -1 .
[0039] The preparation of the active material coal-based porous graphene-like carbon material of the positive electrode plate includes the following steps: (1) Heat the coal material at a rate of 9 °C / min - 20 °C / min to 700 °C and keep it warm for 2 h for pre-carbonization to obtain pre-carbonized carbon powder; (2) Mix the pre-carbonized carbon powder obtained in step (1) and potassium hydroxide in a mass ratio of 1:6, and then heat it to an activation temperature of 960 °C in an inert atmosphere (such as argon), keep it warm for 2 h, and then cool it to room temperature to obtain a porous graphene carbon material; (3) Wash and remove impurities from the porous graphene carbon material obtained in step (2) with HCl and HF, and then wash it with deionized water until it is neutral and then dry it to obtain a coal-based porous graphene-like carbon material.
[0040] The capacitor assembly method is as follows: Positive electrode preparation: Mix the coal-based porous graphene-like carbon material, conductive agent, and binder in a mass ratio of 6:1:1 and grind them into a film. Vacuum dry the film at 105 °C for 14 h, and tear off a 1.1 mg film to obtain a single-piece electrode of about 1 cm², which is the positive electrode plate; in the above scheme, the conductive agent uses conductive carbon black; the binder uses polyvinylidene fluoride; Preparation of the negative electrode sheet: Weigh the negative electrode material, acetylene black, and polyvinylidene fluoride according to a mass ratio of 85:10:10, then add 1-methyl-2-pyrrolidone to form a slurry, coat it on the current collector, and dry it in vacuum at 90 °C for 12 h; among them, the current collector of the negative electrode sheet is one of copper foil, aluminum foil, carbon paper, and carbon cloth, and the total volume of the negative electrode material, acetylene black, and polyvinylidene fluoride is equal to the volume of 1-methyl-2-pyrrolidone.
[0041] Assembly: Under the atmosphere of high-purity argon, assemble the negative electrode sheet, the separator containing the electrolyte, and the positive electrode sheet in sequence to form the sodium-ion capacitor with the coal-based porous graphene carbon material as the positive electrode. This sodium-ion capacitor is a button-type sodium-ion capacitor.
[0042] After testing, the maximum energy density of the sodium-ion capacitor obtained in this example is 105 Wh / kg, and the maximum power density is 8.75 kW / kg.
[0043] Example 3 The sodium-ion capacitor with the coal-based porous graphene carbon material as the positive electrode in this example includes: a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. The active material of the positive electrode sheet uses the coal-based porous graphene carbon material; the negative electrode material of the negative electrode sheet uses lithium titanate; the hybrid capacitor is assembled in the order of the negative electrode sheet, the separator containing the electrolyte, and the positive electrode sheet to form the sodium-ion capacitor with the coal-based porous graphene carbon material as the positive electrode.
[0044] The separator uses glass fiber. Use a pipette to drop the electrolyte onto the glass fiber separator so that the electrolyte fills the pores of the glass fiber separator to obtain the separator containing the electrolyte; the electrolyte uses an organic electrolyte suitable for sodium ion transport. This electrolyte uses sodium hexafluorophosphate (NaPF 6 ) as the salt and is dissolved in a mixed solution of ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC). In this mixed solution, ethylene carbonate, diethyl carbonate, and dimethyl carbonate are mixed in equal volume ratios; in the electrolyte, the concentration of sodium hexafluorophosphate is 1.05 mol L -1 .
[0045] The preparation of the active material coal-based porous graphene carbon material of the positive electrode sheet includes the following steps: (1) Heat the coal material at a rate of 10 °C / min - 20 °C / min to 710 °C and keep it warm for 1 h for pre-carbonization to obtain pre-carbonized carbon powder; (2) Mix the pre-carbonized carbon powder obtained in step (1) and potassium hydroxide in a mass ratio of 1:5, then heat it to an activation temperature of 970 °C in an inert atmosphere (such as argon), keep it warm for 1.5 h, and then cool it to room temperature to obtain a porous graphene carbon material; (3) Wash and remove impurities from the porous graphene carbon material obtained in step (2) with HCl and HF, then wash it with deionized water until neutral and dry it to obtain a coal-based porous graphene-like carbon material.
[0046] The method for assembling the capacitor is as follows: Preparation of the positive electrode: Mix the coal-based porous graphene-like carbon material, conductive agent, and binder in a mass ratio of 7:1:1 and grind them into a film. Vacuum dry the film at 115 °C for 10 h, and tear off a 0.9 mg film to obtain a single-piece electrode of about 1 cm², which is the positive electrode plate; in the above solution, the conductive agent is carbon nanotubes; the binder is 60% polytetrafluoroethylene emulsion; Preparation of the negative electrode plate: Weigh the negative electrode material, acetylene black, and polyvinylidene fluoride in a mass ratio of 80:10:10, then add 1-methyl-2-pyrrolidone to form a slurry, coat it on the current collector, and vacuum dry it at 70 °C for 15 h; among them, the current collector of the negative electrode plate is one of copper foil, aluminum foil, carbon paper, and carbon cloth, and the total volume of the negative electrode material, acetylene black, and polyvinylidene fluoride is equal to the volume of 1-methyl-2-pyrrolidone.
[0047] Assembly: Under the atmosphere of high-purity argon, assemble the negative electrode plate, the separator containing the electrolyte, and the positive electrode plate in sequence to form the sodium-ion capacitor with the coal-based porous graphene-like carbon material as the positive electrode. This sodium-ion capacitor is a button-type sodium-ion capacitor.
[0048] After testing, the maximum energy density of the sodium-ion capacitor obtained in this example is 102 Wh / kg, and the maximum power density is 8.75 kW / kg.
[0049] Example 4 The sodium-ion capacitor with the coal-based porous graphene-like carbon material as the positive electrode in this example includes: a positive electrode plate, a negative electrode plate, a separator, and an electrolyte. The active material of the positive electrode plate is the coal-based porous graphene-like carbon material; the negative electrode material of the negative electrode plate is hard carbon; the hybrid capacitor is assembled into the sodium-ion capacitor with the coal-based porous graphene-like carbon material as the positive electrode in the order of the negative electrode plate, the separator containing the electrolyte, and the positive electrode plate.
[0050] The separator uses glass fiber. Use a pipette to drop the electrolyte onto the glass fiber separator so that the electrolyte fills the pores of the glass fiber separator to obtain the separator containing the electrolyte; the electrolyte uses an organic electrolyte suitable for sodium ion transmission. This electrolyte uses sodium hexafluorophosphate (NaPF 6 ) as the salt and is dissolved in a mixed solution of ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC). In this mixed solution, ethylene carbonate, diethyl carbonate, and dimethyl carbonate are mixed in an equal volume ratio; in the electrolyte, the concentration of sodium hexafluorophosphate is 1.0 mol L-1 。
[0051] The preparation of the active material, coal-based porous graphene-like carbon material, of the positive electrode plate includes the following steps: (1) Heat the coal material at a rate of 8 °C / min - 20 °C / min to 690 °C and keep it warm for 2 h for pre-carbonization to obtain pre-carbonized carbon powder; (2) Mix the pre-carbonized carbon powder obtained in step (1) and potassium hydroxide in a mass ratio of 1:5, and then heat it to 980 °C for activation in an inert atmosphere (such as argon), keep it warm for 1 h and then cool it to room temperature to obtain porous graphene carbon material; (3) Wash and remove impurities from the porous graphene carbon material obtained in step (2) with HCl and HF, then wash it with deionized water until neutral and dry it to obtain coal-based porous graphene-like carbon material.
[0052] The method for assembling the capacitor is as follows: Preparation of the positive electrode: Mix the coal-based porous graphene-like carbon material, conductive agent, and binder in a mass ratio of 8:1:1 and grind them into a film, dry it in vacuum at 115 °C for 12 h, tear off a 1.0 mg film, and prepare a single-piece electrode of about 1 cm², which is the positive electrode plate; in the above scheme, the conductive agent is acetylene black; the binder is sodium carboxymethyl cellulose; Preparation of the negative electrode plate: Weigh the negative electrode material, acetylene black, and polyvinylidene fluoride in a mass ratio of 75:10:10, then add 1-methyl-2-pyrrolidone to form a slurry, coat it on the current collector, and dry it in vacuum at 60 °C for 18 h; among them, the current collector of the negative electrode plate is one of copper foil, aluminum foil, carbon paper, and carbon cloth, and the total volume of the negative electrode material, acetylene black, and polyvinylidene fluoride is equal to the volume of 1-methyl-2-pyrrolidone Assembly: Under the atmosphere of high-purity argon, assemble the negative electrode plate, the separator containing the electrolyte, and the positive electrode plate in sequence into the sodium-ion capacitor with the coal-based porous graphene-like carbon material as the positive electrode. This sodium-ion capacitor is a button-type sodium-ion capacitor.
[0053] After testing, the maximum energy density of the sodium-ion capacitor obtained in this example is 98 Wh / kg, and the maximum power density is 8.75 kW / kg.
[0054] Obviously, the described embodiments are only partial embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the scope of protection of the present invention.
[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit them. Although the present invention has been described in detail with reference to the above embodiments, those of ordinary skill in the art should understand that: it is still possible to modify the specific implementation manners of the present invention or make equivalent replacements, and any modifications or equivalent replacements that do not depart from the spirit and scope of the present invention shall be covered within the scope of the present invention.
Claims
1. A sodium ion capacitor with a coal-based porous graphene-like carbon material as a positive electrode, characterized in that: It includes a negative electrode plate, a diaphragm containing an electrolyte is provided on the surface of the negative electrode plate, a positive electrode plate is provided on the surface of the diaphragm containing an electrolyte, and the active material of the positive electrode plate adopts a coal-based porous graphene-like carbon material; the negative electrode material of the negative electrode plate adopts graphite, hard carbon, soft carbon, lithium titanate, niobium-based oxide, niobium-based metal oxide or titanium niobium oxide material; in the diaphragm containing an electrolyte, the electrolyte adopts an organic solution of sodium hexafluorophosphate.
2. A sodium ion capacitor with a coal-based porous graphene-like carbon material as a positive electrode according to claim 1, characterized in that: The preparation process of the positive electrode sheet includes: The coal-based porous graphene-like carbon material, the conductive agent and the binder are mixed and ground into a film, and then vacuum dried to obtain the positive electrode plate.
3. A sodium ion capacitor with a coal-based porous graphene-like carbon material as a positive electrode according to claim 2, characterized in that: The mass ratio of coal-based porous graphene-like carbon material, conductive agent and binder is (6-8):1:1, and the surface density of the positive electrode sheet is 0.9~1.1g / cm 2 .
4. A sodium ion capacitor with a coal-based porous graphene-like carbon material as a positive electrode according to claim 2, characterized in that: The conductive agent is one of conductive carbon black, acetylene black and carbon nanotubes.
5. A sodium ion capacitor with a coal-based porous graphene-like carbon material as a positive electrode according to claim 2, characterized in that: The binder is one of polyvinylidene fluoride, polytetrafluoroethylene and sodium carboxymethyl cellulose.
6. A sodium ion capacitor with a coal-based porous graphene-like carbon material as a positive electrode according to claim 1, characterized in that: The preparation process of coal-based porous graphene-like carbon materials includes: The coal material is heated to 690-710°C at a heating rate of 8-10°C / min and kept at this temperature for 1-2 h to obtain pre-carbonized carbon powder; The pre-carbonized carbon powder and potassium hydroxide are mixed in a mass ratio of 1: (4-6), and then heated to 950-980°C in an inert atmosphere for activation for 1-2 hours, and then cooled after the insulation to obtain a porous graphene carbon material; The porous graphene carbon material is repeatedly washed with hydrochloric acid and hydrofluoric acid for 3 to 5 times, then washed with deionized water until the solution is neutral, and then dried to obtain the coal-based porous graphene-like carbon material.
7. A sodium ion capacitor with a coal-based porous graphene-like carbon material as a positive electrode according to claim 1, characterized in that: The diaphragm is a glass fiber diaphragm, and the electrolyte is filled in the pores of the glass fiber diaphragm; In the electrolyte, the organic solution is a solution of ethylene carbonate, diethyl carbonate and dimethyl carbonate mixed in equal volume ratio, and the concentration of sodium hexafluorophosphate is 0.95~1.05 mol L -1 .
8. The sodium ion capacitor with coal-based porous graphene-like carbon material as positive electrode according to claim 1, characterized in that: The preparation process of the negative electrode sheet includes: The negative electrode material, acetylene black and polyvinylidene fluoride are added to 1-methyl-2-pyrrolidone to form a slurry, which is coated on a current collector and then vacuum dried to obtain a negative electrode sheet; wherein the mass ratio of the negative electrode material, acetylene black and polyvinylidene fluoride is (75~85):10:
10.
9. The sodium ion capacitor with coal-based porous graphene-like carbon material as positive electrode according to claim 1, characterized in that: The negative electrode material, acetylene black and polyvinylidene fluoride are added to 1-methyl-2-pyrrolidone in an equal mass ratio to form a slurry, and the total volume of the negative electrode material, acetylene black and polyvinylidene fluoride is equal to the volume of 1-methyl-2-pyrrolidone.
10. A method for preparing a sodium ion capacitor with a coal-based porous graphene-like carbon material as a positive electrode according to any one of claims 1 to 9, comprising: In a protective atmosphere, a negative electrode sheet, a diaphragm containing an electrolyte, and a positive electrode sheet are assembled in order to obtain the sodium ion capacitor with the coal-based porous graphene-like carbon material as the positive electrode.